O novo currículo de Geografia para o Estado de São Paulo: uma análise crítica - Gebran, Raimunda Abou (Revista Cocar, 2015)
O presente trabalho teve por objetivo analisar o novo Currículo de Geografia do Estado de São Paulo, especificamente do 6º ao 9º ano do Ensino Fundamental, implementado a partir de 2008 nas escolas da rede estadual para o Ensino Fundamental e Médio. A pesquisa se configurou numa perspectiva qualitativa, apoiada na análise documental. Para tanto, os documentos oficiais da Secretaria da Educação (legislação, a própria proposta, Caderno do Professor, Caderno do Aluno) constituíram subsídios fundamentais para a análise documental. Após a análise, foi possível entender que esta nova proposta se constitui em um suporte pedagógico de extrema importância para o professor que atua na rede oficial de ensino. Contudo, se fazem necessárias e permanentes a revisão e rediscussão pelos sujeitos envolvidos, em especial pelos docentes, para que a Proposta Curricular não se configure como um modelo a ser seguido e respeitado, sem possibilidades de mudanças. Palavras-chave: Currículo. Ensino da Geografia. Ensino Fundamental. The new são paulo state geography curriculum: a critical analysis This study aimed to analyze the new curriculum of the State of São Paulo Geography, specifically from 6th to 9th grade of elementary school , implemented from 2008 in schools of" the state system for primary and secondary education. Taking into account the field of studies and researches conducted by the author, the analyses focused on the proposal meant for the teaching of Geography, mainly at the level comprising from the 6th to the 9th grade. The research was presented within a qualitative perspective based on documental analysis. Therefore, official documents issued by the State Education Department (legislation, the proposal at issue, teacherâ€™s and studentâ€™s copybooks) were fundamental subsidies for the documental analysis, from whose basis the analysis classes were brought about. After the analysis, one managed to understand that this new proposal is a very important pedagogical support for teachers who work in the state public school network. However, one holds as necessary and continuing the review and" new discussions by the subjects involved in it, namely the teachers, so that the proposed curriculum design does not become a model to be followed and respected without being subject to changes. Keywords: Curriculum design proposal. Teaching of Geography. Elementary School.